A systematic review of treatment strategies for erythrodermic psoriasis. (2nd January 2021) - Reynolds, Kelly A.; Pithadia, Deeti J.; Lee, Erica B.; Liao, Wilson; Wu, Jashin J.
Abstract: Background: Erythrodermic psoriasis (EP) is a severe, rare form of psoriasis that can be life threatening. Treatment of EP is usually based on anecdotal evidence or past clinical experience, which is in part due to the rarity and often emergent nature of this psoriasis subtype. Methods: In December 2018, a keyword search for 'erythrodermic psoriasis' and 'treatment' was conducted. All studies investigating treatment strategies for EP in at least 2 patients were included in this review. Results: The database search yielded 921 results, and 23 studies comprising over 200 patients with EP were included in the final analysis. Biologics including tumor necrosis factor inhibitors (infliximab [ n = 4], etanercept [ n = 2], and adalimumab [ n = 1]), interleukin-17 inhibitors (secukinumab [ n = 3], ixekizumab [ n = 2], and brodalumab [ n = 1]), ustekinumab ( n = 4), and guselkumab ( n = 1) have been shown to rapidly achieve clinical improvement in patients with EP. The included studies also demonstrated efficacy of systemic agents cyclosporine ( n = 4), etretinate ( n = 3), and methotrexate ( n = 1). Conclusions: A fair number of poor-quality studies support the use of various biologic and systemic therapies in the treatment of EP. Treatment of EP should be based on the severity of the clinical scenario as well as patient comorbidities.